Double trouble – primary biliary cholangitis and coeliac disease in a young female: a case report - Ikramullah; Eyan Khan; Khushal Khan; Awais Naeem; Fahad Naim; Rehman, Aisha (Journal of the Pakistan Medical Association, 2023)
In this case report, we describe a patient who was diagnosed with both Primary Biliary Cholangitis and Coeliac Disease, presenting with symptoms and signs of severe malabsorption and portal hypertension. Extensive workup was done including duodenal and liver biopsies and our patient was ultimately found to have both autoimmune diseases. An association between the two diseases has been reported multiple times during the past four decades with current guidelines recommending screening patients with primary biliary cholangitis for coeliac disease. Keywords: Celiac Disease, Primary Biliary Cholangitis, Malabsorption, Portal Hypertension.